2010
DOI: 10.1038/jcbfm.2010.195
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Attenuates Blood–Brain Barrier Disruption in a Rat Model of Transient Focal Cerebral Ischemia: The Roles of HDAC and MMP-9 Inhibition

Abstract: Valproic acid (VPA), a histone deacetylase (HDAC) inhibitor, is known to protect against cerebral ischemia. The effects of VPA on blood-brain barrier (BBB) disruption were investigated in rats subjected to transient middle cerebral artery occlusion (MCAO). Postischemic VPA treatment remarkably attenuated MCAO-induced BBB disruption and brain edema. Meanwhile, VPA significantly reduced MCAO-induced elevation of matrix metalloproteinase-9 (MMP-9), degradation of tight junction proteins, and nuclear translocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
180
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(188 citation statements)
references
References 15 publications
7
180
1
Order By: Relevance
“…These results indicated that the mechanism underlying BBB protection may be associated with the inhibition of AQP-4 and MMP-9 function. Studies have additionally demonstrated that propofol inhibited the expression of AQP-4 in astroglia in vitro (23) and decreased the expression of MMP-9 in vivo (24). In the present study, the expression levels of AQP-4 and MMP-9 were markedly lower in groups P1 and P2 than those in group S, indicating that treatment with propofol inhibited the expression of these proteins.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…These results indicated that the mechanism underlying BBB protection may be associated with the inhibition of AQP-4 and MMP-9 function. Studies have additionally demonstrated that propofol inhibited the expression of AQP-4 in astroglia in vitro (23) and decreased the expression of MMP-9 in vivo (24). In the present study, the expression levels of AQP-4 and MMP-9 were markedly lower in groups P1 and P2 than those in group S, indicating that treatment with propofol inhibited the expression of these proteins.…”
Section: Discussionmentioning
confidence: 45%
“…Inhibitors of AQP-4 and MMP-9 may protect the BBB to a certain extent (20). The extent of brain edema observed in cerebral ischemia/reperfusion animals was significantly reduced following inhibition, and the animals demonstrated an improved prognosis (21)(22)(23). These results indicated that the mechanism underlying BBB protection may be associated with the inhibition of AQP-4 and MMP-9 function.…”
Section: Discussionmentioning
confidence: 56%
“…In and around the ischemic core, a general decrease of histone H3 acetylation [46][47][48][49][50] as well as of H4 acetylation levels [51][52][53][54] was identified in multiple studies. Vast deacetylation processes occur quickly upon an ischemic insult and induce a fatal course of events.…”
Section: Dna Methylationmentioning
confidence: 99%
“…The DX+RT group received 100 mg/kg intramuscular (IM) DX monohydrate solution (200 mg per mL ready solution for injection) (Doksilin LA, Provet; İstanbul, Turkey). The VA dose required for MMP inhibition was determined on the basis of that reported in a previous study (14). DX was administered as a single dose of 100 mg/kg since the recommended DX longacting injectable dose was 70-100 mg/kg in rat medication (15).…”
Section: Methodsmentioning
confidence: 99%